Music cognition and the bodily approach: Musical instruments as tools for musical semantics. - Reybrouck, Mark (Contemporary Music Review, 2006)
This article is about music cognition and the role the body plays in its acquisition. It argues for a processual approach to dealing with music rather than conceiving of music as an artefact. Leaning heavily on the older philosophical writings of Dewey, it tries to provide an operational approach to the musical experience, with a special focus on the sensory-motor interactions of the music user with the sonic world. As such, it is possible to conceive of the music user as an adaptive device, with natural perceptual and effector tools that can be modified at will. It is argued, further, that musical instruments can be considered as artificial extensions of these natural tools, allowing us to conceive of them in epistemological terms as tools for music knowledge acquisition.